Characteristics and Prevention Measures of Loess Geological Disasters in Longdong Region. Issue 4 (March 2020) - Yang, Yang; Liu, Wanfeng; Hu, Aiping; Zhang, Binwei; Yang, Hongping
Abstract: In recent years, loess geological disasters in Longdong region occurred more and more frequently. On the basis of investigation on loess geological disasters in Longdong region and analysis of basic physical characteristics of loess geological disasters, landslide, collapse, debris flow and loess collapsibility are identified as the main geological disasters in Longdong region. The causes of four types of loess geological disasters in Longdong region are studied and corresponding prevention measures are proposed.